THE TEACHING OF SINCERE AND PATIENCE: BEHAVIORAL VALUES FOR GRADES OF ISLAMIC JUNIOR HIGH SCHOOL - Dimas, Septian; Hadi, Jamaluddin; M. Mahbubi (International Journal of Multidisciplinary Reseach, 2025)
This Research aims to describe the procces of sincerely value teaching and patience in Behavioral Lesson of Nurul Hasyimi Islamic Junior High School on each grade. Those values consider as an urgent part on character-building of student at Junior High School level. The method that use for the approachment is qualitative descriptive by data-mining through observation, interview and documentation. The results shows that behavioral lesson teacher actively use contextual-teaching methode with speech, discussion and moral stories of Islam History. The sincere values tough as a charity attitude without any compliment, besides patience understood as ability of self-control in facing life problem. Student gives a positive feedback toward this teaching learning, eventough facing the challange of values implementation on daily life. The supported school environment, strong religious culture and the role of teacher become the main factor of internalization of those values. This research conclude that sincere and patience teaching have an important role in student character-building and need to be upgraded through cooperation among teachers, family and social enviroment.